Time Related Changes in Pathogenic Bacterial Patterns in Burn Wound Infections and Their Antibiotic Sensitivity Traits (Bangladesh Journal of Medical Science, 2017)
Objectives: To examine the time related changes in the bacterial flora isolated from the burn patients and to compare the antibiograms of the predominant bacteria. Burn injuries constitute a major health concern with respect to morbidity and mortality as well as cost of management particularly in developing countries. It has been estimated that 75% of all deaths following thermal injuries are related to infection. It is essential for every hospital to determine the specific pattern of burn wound microbial colonization, time-related changes in predominant flora and anti microbial sensitivity profiles.Materials and Methods: 60 burn patients and their microbial isolates were examined during the study period. Periodic swabs were taken from burn wounds of the patients on admission and on 7th, 14th, and 21st days of hospitalization and the isolates were processed for culture, identification and antimicrobial sensitivity as per CLSI guidelines.Results: Among the 240 samples, single organism was isolated in 161 samples (67.1%) and mixed organisms in 22 samples (9.1 %) and no growth in 57 samples (23.7%). Among single isolates pseudomonas aerugenosa was predominant species (20.8%) followed by acinetobacter baumanii (15.4%), staph. aureus (14.1%) and klebsiella (7.5%). Among mixed growth pseudomonas was predominant species (30.4%) followed by acinetobacter (23.9%). klebsiella (17.4 %) and staph. aureus (10.8%). There was time related changes in bacterial isolation from burn wound during hospital stay of patients. On admission, Staph. Aureus was 18.3 %, pseudomonas was 8.3% and klebsiella was 6.6%. No growth found in 48.3% samples. These findings gradually changed with time and on day 21 Pseudomonas was 30% followed by Acinetobacter sp. (21.6%), Staph. aureus (13.3%) and Klebsella pneumoniae (6.6%). No growth was seen in 15% cases only. Antimicrobial sensitivity test showed that pseudomonas was sensitive to Imipenem, Merepenem and Ampicillin. Acinetobacter was also found most sensitive to Amikacin and Tetracycline, followed by Tobramycin. Staphylococcus aureus was sensitive to Linezolid, Gentamycin followed by Vancomycin.Conclusion: There were timerelated changes in microbial colonization during hospital stay of patients. Effective protocols should be made for burn patients and effort is needed for improving overall infection related morbidity and mortality.Bangladesh Journal of Medical Science Vol.16(2) 2017 p.295-301